2022
DOI: 10.1002/pbc.29958
|View full text |Cite
|
Sign up to set email alerts
|

Body image in adolescent survivors of childhood cancer: The role of chronic health conditions

Abstract: Background Cancer and its treatment may impair the body image of childhood cancer survivors during adolescence. We compared the body image between adolescent cancer survivors and their siblings, and determined whether survivors’ body image is associated with socio‐demographic characteristics, clinical characteristics and chronic health conditions. Procedure As part of the nationwide Swiss Childhood Cancer Survivor Study, we sent questionnaires to adolescents (aged 16–19 years), who survived >5 years after havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Finally, three parents and two children spontaneously spoke of body image concerns and a lack of body acceptance with examples including hair loss, steroid-related "moon face," and dramatic changes to height and weight. These comments align with previous literature indicating that subsets of children who survive cancer have poorer body image than healthy controls, particularly those with chronic health conditions (i.e., OW/ OB; Belle et al, 2022).…”
Section: Mental Health Concernssupporting
confidence: 89%
“…Finally, three parents and two children spontaneously spoke of body image concerns and a lack of body acceptance with examples including hair loss, steroid-related "moon face," and dramatic changes to height and weight. These comments align with previous literature indicating that subsets of children who survive cancer have poorer body image than healthy controls, particularly those with chronic health conditions (i.e., OW/ OB; Belle et al, 2022).…”
Section: Mental Health Concernssupporting
confidence: 89%
“…The signi cance of managing appearance-related side effects in cancer survivors has recently been recognized [12,13], with a pressing need to reduce the incidence of short stature in CCS. Our study found that up to 8 out of 17 CCS were below 150 cm in height, highlighting the need for a management policy to prevent short stature.…”
Section: Discussionmentioning
confidence: 99%
“…If at least one corresponding CHC was present, we classi ed survivors as having an affected organ system. If information about health conditions was missing, we assumed conditions were not present, as done previously [32].…”
Section: Outcome: Chronic Health Conditionsmentioning
confidence: 99%